Extracellular matrix-imitating anti-inflammatory nerve repair-promoting conductive hydrogel as well as preparation method and application thereof

By modifying MXene nanosheets and mixing them with chitosan and gelatin to form a conductive hydrogel, the problem of insufficient conductivity of traditional hydrogels is solved, and excellent conductivity and anti-inflammatory and pro-neurological repair functions are achieved.

CN119859289AActive Publication Date: 2025-04-22JILIN UNIVERSITY

Patent Information

Application Number
CN202510090341.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-21
Publication Date
2025-04-22
Estimated Expiration
2045-01-21

AI Technical Summary

Technical Problem

Traditional chemical crosslinked hydrogels have insufficient electrical conductivity, limiting their use in applications requiring electroactive activity.

Method used

By preparing the MXene nanosheet dispersion, polyphenols and magnesium ions were added to the reaction, and after modification, mixed with chitosan and gelatin to form a conductive hydrogel.

Benefits of technology

The resulting conductive hydrogel has components, structure, mechanical elasticity and excellent conductivity similar to the extracellular matrix, and has anti-inflammatory and pro-neurological repair functions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119859289A_ABST
    Figure CN119859289A_ABST
Patent Text Reader

Abstract

The invention discloses an extracellular matrix-imitated anti-inflammatory nerve repair-promoting conductive hydrogel as well as a preparation method and application thereof, and belongs to the technical field of high polymer materials. The preparation method of the conductive hydrogel comprises the following steps: preparing an MXene nanosheet dispersion liquid, and sequentially adding polyphenol and magnesium ions into the MXene nanosheet dispersion liquid to obtain a modified nanosheet solution; mixing the modified chitosan with polyvinyl alcohol to obtain a solution A; mixing and reacting the modified nanosheet solution with phenylboronic acid modified gelatin to obtain a solution B; mixing the solution A and the solution B for reaction, refrigerating at low temperature, and unfreezing to obtain the conductive hydrogel. The hydrogel prepared by the invention has excellent conductivity, and the obtained conductive hydrogel has the functions of resisting inflammation and promoting nerve repair. The bionics method not only improves the diversity and functionality of biological materials, but also provides new possibility for future tissue engineering and regenerative medicine.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, and in particular to an extracellular matrix-mimicking, anti-inflammatory, nerve-repair-promoting conductive hydrogel, and a preparation method and application thereof. Background Art

[0002] Bionic thinking can well expand the diversity of biomaterials. It is well known that the extracellular matrix (ECM) is a very complex fluid environment, which not only supports the growth and differentiation of cells as a three-dimensional scaffold, but also controls cell behavior by regulating dynamic mechanical and chemical signals and their microenvironment, and promotes tissue repair during injury. In recent years, hydrogel, as a three-dimensional material with high water content, has developed most rapidly in the field of biological tissue repair. Hydrogel has good biocompatibility and adjustable physical properties, making it an ideal choice for simulating natural ECM.

[0003] However, hydrogels themselves are not conductive, which limits their use in certain applications that require electrical activity. Conductive hydrogels form endogenous electric fields, which significantly promote angiogenesis, nerve repair and tissue healing, and can therefore be widely used to repair electrically active tissues such as wounds, myocardium and nerves. The organic combination of conductive hydrogels with hydrophilic matrices and conductive media is a new type of composite hydrogel with good processability, high flexibility and excellent electrochemical properties. It has broad application prospects in many fields such as electronic skin, biosensors, supercapacitors, and flexible wearable electronic devices, and is an ideal material for future flexible electronic devices. However, most traditional chemically cross-linked hydrogels have the problem of insufficient conductivity, which is also the key to limiting the application of hydrogels. Therefore, it is of great significance to provide a hydrogel preparation scheme with excellent conductive properties. Summary of the invention

[0004] The purpose of the present invention is to provide an extracellular matrix-like anti-inflammatory and nerve repair-promoting conductive hydrogel and its preparation method and application to solve the problems existing in the above-mentioned prior art. The hydrogel prepared by the present invention has similar components, structure, mechanical elasticity and excellent conductive properties to the extracellular matrix, and the obtained conductive hydrogel has the functions of anti-inflammatory and nerve repair.

[0005] In order to solve the above problems, the present invention provides the following solutions:

[0006] Technical solution 1: A method for preparing a conductive hydrogel, comprising the following steps: preparing a MXene nanosheet dispersion, adding polyphenol and magnesium ions to the MXene nanosheet dispersion in sequence to react, to obtain a modified nanosheet solution; mixing the modified chitosan with polyvinyl alcohol to obtain a solution A; mixing the modified nanosheet solution with gelatin modified with phenylboronic acid to obtain a solution B; mixing and reacting solution A with solution B, then refrigerating at low temperature, and obtaining the conductive hydrogel after thawing.

[0007] Furthermore, the modified nanosheet solution is prepared, comprising the following steps: adding LiF to a hydrochloric acid solution, adding Ti3AlC2 and mixing; collecting the mixed precipitate, centrifuging and washing with deionized water until the pH value of the supernatant reaches 6; collecting the sediment obtained after centrifugation, ultrasonically dispersing under an Ar environment and then centrifuging, collecting the solution, and obtaining a MXene nanosheet dispersion; dropping a gallic acid or tannic acid solution into the MXene nanosheet dispersion for mixing and reaction, and then dropping a MgCl2·6H2O solution, mixing, centrifuging and washing, to obtain the modified nanosheet solution.

[0008] Specifically, the preparation of the modified nanosheet solution includes the following steps: taking 1 to 3 g of LiF and adding it to 20 to 60 mL of 9 to 10 M hydrochloric acid solution and stirring it thoroughly; then slowly adding 1 to 3 g of Ti3AlC2 and stirring it at 35 to 45°C for 24 to 28 hours; collecting the precipitate and centrifuging it at 4500 rpm with deionized water for 5 to 10 minutes until the pH value of the supernatant reaches 6; then collecting the sediment and adding 50 to 100 mL of deionized water and ultrasonically dispersing it under Ar environment for 1 to 1.5 hours, and then centrifuging and collecting the solution, dissolving 10 to 50 mg of gallic acid or tannic acid in Tris at pH = 8.5, and then slowly dropping it into 10 mg / mL of MXene nanosheet dispersion and stirring it in the dark for 2 to 4 hours. Then, 50-100 mg of MgCl2·6H2O is added to 1-5 mL of Tris solution and added dropwise to the previous solution for reaction, stirring is continued, and finally, the mixture is centrifuged at 8000-10000 speed for 3-10 minutes, and the precipitate is washed and collected with deionized water to obtain the modified nanosheet solution.

[0009] Furthermore, the preparation method of the modified chitosan comprises the following steps: dissolving dihydrocaffeic acid and adding it to a chitosan solution to obtain a mixed solution 1; dissolving 1-ethyl-(3-dimethylaminopropyl)carbodiimide and N-hydroxysulfosuccinimide in a mixed solution of ethanol and deionized water to obtain a mixed solution 2, adding the mixed solution 2 to the mixed solution 1 for reaction, introducing Ar and reacting to obtain a product solution, first dialyzing it in acidified deionized water, then dialyzing it in deionized water, and finally freeze-drying it.

[0010] Specifically, the preparation method of the modified chitosan comprises the following steps: dissolving 0.5-0.8g chitosan in deionized water, adjusting the pH to 5.0-6.0 by HCl, and stirring in a water bath at 60-80°C for 20-30min; dissolving 255-455mg dihydrocaffeic acid in 5.0-8.0mL deionized water, stirring and dissolving the mixture, and then adding the mixture to the chitosan solution; dissolving 240-300mg 1-ethyl-(3-dimethylaminopropyl)carbodiimide and 150-200mg N-hydroxysulfosuccinimide in a mixed solution of 50.0mL ethanol and deionized water in a ratio of 1:1-1:2, adding the mixture to the mixed solution, and reacting the mixture for 12h at room temperature after passing Ar; dialyzing the product solution in acidified deionized water for 2-3 days, then dialyzing it in deionized water for another 0.5 day, and finally freeze drying the mixture in a freeze dryer.

[0011] Furthermore, the preparation method of the modified gelatin comprises the following steps:

[0012] Add 4-8 g of gelatin to 400-800 mL of deionized water at 60-80° C. and stir thoroughly. Add 7-10 g of NHS and 1.5-3 g of EDS powder to the above solution and stir evenly. Adjust the pH to 5 with 1-5 M hydrochloric acid solution. Then add 3-6 g of PBA powder and stir in a water bath at 37-45° C. for 48 hours. Then, dialyze the obtained solution in deionized water for 3 days and freeze-dry.

[0013] Furthermore, the preparation method of the solution A comprises: dissolving the polyvinyl alcohol powder, adding the modified chitosan into the dissolved polyvinyl alcohol solution, and mixing and reacting to obtain the solution A.

[0014] The specific preparation method of the solution A is as follows: 1-3 g of PVA powder is added to 10-30 mL of deionized water solution and dissolved at 95-100° C., and 0.1-0.3 g of CSDA is added to the dissolved PVA solution and stirred for 1-2 hours to obtain solution A.

[0015] Furthermore, the preparation method of the solution B comprises: preparing a 12.5 wt % solution of phenylboronic acid-modified gelatin, and adding the modified nanosheet solution thereto to obtain the solution B.

[0016] The specific preparation method of the solution B is as follows: prepare a 12.5 wt % solution of phenylboronic acid-modified gelatin, and add 20 to 60 μL of a 10 mg / mL modified nanosheet solution thereto to obtain solution B.

[0017] Furthermore, the solution A and the solution B are mixed and reacted in a volume ratio of 1:1.

[0018] Furthermore, the low-temperature refrigeration is refrigeration at -80°C for 12 to 48 hours.

[0019] Technical solution 2: The conductive hydrogel prepared by the preparation method.

[0020] Technical solution three: Application of the conductive hydrogel in the preparation of a hydrogel having extracellular matrix-mimicking and anti-inflammatory effects.

[0021] Technical Solution 4: Application of the conductive hydrogel in the preparation of a hydrogel that promotes the proliferation and repair of nerve cells.

[0022] The present invention discloses the following technical effects:

[0023] The present invention provides an extracellular matrix-mimicking anti-inflammatory and nerve repair-promoting conductive hydrogel, a preparation method and biological applications thereof. The present invention first prepares MXene nanosheets, and then sequentially adds polyphenols and magnesium ions to the MXene nanosheet solution and stirs; after fully mixing and uniformly washing, the modified nanosheets are obtained, which have the functions of conducting electricity, resisting inflammation and promoting nerve repair. The preparation method comprises mixing the modified chitosan with polyvinyl alcohol to obtain solution A, and mixing the novel nanosheet with the modified gelatin to obtain solution B. After mixing solutions A and B in a certain proportion and reacting, the solutions are refrigerated at low temperature for a period of time to obtain the conductive hydrogel.

[0024] The main raw materials of the hydrogel synthesized by the present invention are widely available, have good biocompatibility and are non-toxic, which is conducive to the commercialization of the product. The hydrogel provided by the present invention has an easy gelation process and a fast gelation speed. The conductive hydrogel provided by the present invention simulates the extracellular matrix and is conducive to tissue repair. The hydrogel prepared by the present invention has components, structures, mechanical elasticity and excellent conductive properties similar to those of the extracellular matrix, and the obtained conductive hydrogel has anti-inflammatory and nerve repair-promoting functions. The method provided by the present invention not only improves the diversity and functionality of biomaterials, but also provides new possibilities for future tissue engineering and regenerative medicine. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0026] Figure 1 The transmission electron microscopy image of the modified nanosheet solution prepared in Example 1, wherein the magnesium ions are evenly distributed on the MXene nanosheet, wherein A is the transmission image of the modified nanosheet, B is the surface O element distribution, C is the Ti element distribution, and D is the Mg element distribution;

[0027] Figure 2 This is a photo of the conductive hydrogel gelation of Example 1;

[0028] Figure 3 The free radical scavenging ability of the hydrogel prepared in Example 1;

[0029] Figure 4 This is an immunofluorescence image of the hydrogel prepared in Example 1 promoting the proliferation and development of neural cells;

[0030] Figure 5 is the relative fluorescence area of ​​the hydrogel prepared in Example 1;

[0031] Figure 6 The conductivity of the hydrogel prepared in Example 2 has an electrical conductivity that matches that of nerve cells. DETAILED DESCRIPTION

[0032] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0033] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0034] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0035] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.

[0036] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0037] EGCG can be expressed as tannic acid or gallic acid.

[0038] Example 1

[0039] 1. Preparation of conductive hydrogel

[0040] (1) Preparation of modified nanosheet solution: 1g LiF was added to 20mL 9M hydrochloric acid solution and stirred thoroughly. Then 1g Ti3AlC2 was slowly added and stirred at 45℃ for 26h. The precipitate was collected and centrifuged at 4500rpm for 5min with deionized water until the pH value of the supernatant reached 6. Then the sediment after centrifugation was collected and added to 60mL deionized water for ultrasonic dispersion under Ar environment for 1h and then centrifuged to collect the solution, which was the MXene nanosheet dispersion. 10mg tannic acid (EGCG) was dissolved in Tris buffer at pH=8.5 and then slowly added to 10mg / mL MXene nanosheet dispersion. After stirring for 2h in the dark, MgCl2·6H2O solution was added to it and continued to stir the reaction. Finally, it was centrifuged at 8000rpm for 5min and the precipitate MXene@EGCG-Mg (modified nanosheet solution) was collected by washing with deionized water. The MgCl2·6H2O solution was obtained by dissolving 50 mg of MgCl2·6H2O in 2 mL of Tris solution.

[0041] (2) Preparation of chitosan modified with catechol groups (CHIC): 0.5 g chitosan was dissolved in deionized water, the pH was adjusted to 5.0 with HCl, and stirred in a water bath at 60°C for 20 min. Then 260 mg HCA (dihydrocaffeic acid) was dissolved in 5.0 mL deionized water, stirred thoroughly and dissolved, and then added to the chitosan solution. 240 mg 1-ethyl-(3-dimethylaminopropyl)carbodiimide EDC and 150 mg N-hydroxysulfosuccinimide NHS were dissolved in a 1:1 mixture of 50.0 mL ethanol and deionized water. Then they were added to the mixed solution, and Ar was introduced and reacted at room temperature for 12 h. The solution was dialyzed in acidified deionized water for 2 days, then dialyzed in deionized water for another 0.5 day, and finally freeze-dried in a freeze dryer to obtain a yellow solid.

[0042] (3) Gelatin modified with phenylboronic acid (GPBA): 4 g of gelatin was added to 400 mL of deionized water at 70°C and stirred thoroughly. 7 g of NHS (N-hydroxysulfosuccinimide) and 2 g of EDS (N-(3-dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride) powder were added to the above solution and stirred evenly, and the pH was adjusted to 5 with hydrochloric acid solution. Then 3.5 g of PBA powder was added and stirred in a water bath at 37°C for 48 h. The resulting solution was dialyzed in deionized water for 3 days and then freeze-dried.

[0043] (4) 1 g of PVA (polyvinyl alcohol) powder was added to 10 mL of deionized water and dissolved at 95 °C, 0.1 g of chitosan modified with catechol groups was added to the dissolved PVA solution and stirred for 1 h to obtain solution A; then GPBA was prepared into a 12.5 wt% solution and 20 μL of 10 mg / mL MXene@EGCG-Mg was added thereto to obtain solution B. Solutions A and B were mixed in a volume ratio of 1:1 and then placed in a -80 °C refrigerator for 12 h, and thawed at room temperature to obtain a conductive hydrogel.

[0044] 2. Conductive hydrogel performance determination

[0045] (1) The electrochemical properties of the hydrogel patch were tested using the double-probe method using an electrochemical workstation (CHI660C). The hydrogel was sandwiched between two copper sheets for measurement. During the impedance measurement, the voltage was kept constant at 50 mV and the frequency range was 10 6 -10 -1 Hz.

[0046] (2) The antioxidant properties of the hydrogel components were tested using the DPPH free radical scavenging method. First, a DPPH solution was prepared and stored in a dark place. Then, the hydrogel was prepared into a 2.0 mg / mL solution. After the DPPH solution was mixed with 100 μL of the sample solution, it was placed in the dark for 30 to 120 minutes. Finally, the solution was scanned using an ELISA reader.

[0047] (3) After 7 days of culture, PC12 cells were washed 3 times with PBS, fixed with 4% paraformaldehyde for 20 minutes, and permeabilized with 0.3% TritonX-100 for 5 minutes. After blocking with 1% BSA for 1 hour, cells were incubated with diluted primary antibody (Tuj1) at 4°C overnight, and then incubated with secondary antibody at room temperature for 1 hour. Cells were washed 3 times with PBS and stained with DAPI staining solution for 5 minutes. Finally, cells were examined with a laser scanning confocal microscope.

[0048] 3. Experimental results

[0049] The transmission electron microscopy image of the prepared MXene@EGCG-Mg nanosheets is shown in Figure 1(200nm), it can be seen that magnesium ions are evenly distributed on the MXene nanosheets; the photo of conductive hydrogel formation is shown in Figure 2 The free radical scavenging ability of the prepared hydrogel is shown in Figure 3 ; The immunofluorescence image of the prepared hydrogel promoting the proliferation and development of neural cells is shown in Figure 4 The PCP group represents the hydrogel with a nanosheet concentration of 0 mg / mL, and the PCPM2 group represents the hydrogel with a nanosheet concentration of 0.4 mg / mL; the relative fluorescence area is shown in Figure 5 , PCP group represents hydrogel with nanosheet concentration of 0 mg / mL. In summary, the conductive hydrogel prepared by the present invention has high conductivity and free radical scavenging ability, and can promote the proliferation of nerve cells.

[0050] Example 2

[0051] 1. Preparation of conductive hydrogel

[0052] (1) First, take 2g of LiF and add it to 40mL of 10M hydrochloric acid solution and stir it thoroughly. Then slowly add 2g of Ti3AlC2 and stir it at 35℃ for 28h. Collect the precipitate and centrifuge it at 4500rpm for 8min with deionized water until the pH value of the supernatant reaches 6. Then collect the sediment and add 100mL of deionized water and ultrasonically disperse it under Ar environment for 1.5h and then centrifuge to collect the solution. Dissolve 50mg of gallic acid (EGCG) in Tris buffer with pH=8.5 and then slowly add it to 10mg / mL of MXene nanosheet dispersion and stir it for 2h in the dark. Then add 60mg of MgCl2·6H2O to 2mL of Tris solution and add it to the previous solution and continue to stir the reaction. Finally, centrifuge it at 10000rpm for 5min and wash it with deionized water to collect the precipitate MXene@EGCG-Mg (modified nanosheet solution).

[0053] (2) 0.8 g of chitosan was dissolved in deionized water, the pH was adjusted to 5.0 with HCl, and stirred in a water bath at 80°C for 30 min. Then 455 mg of HCA was dissolved in 8.0 mL of deionized water, stirred thoroughly and dissolved, and then added to the chitosan solution. 300 mg of 1-ethyl-(3-dimethylaminopropyl)carbodiimide EDC and 200 mg of N-hydroxysulfosuccinimide NHS were dissolved in a 1:1 mixture of 50.0 mL of ethanol and deionized water. Then, they were added to the mixed solution, and after passing Ar, the mixture was reacted at room temperature for 12 h. The solution was dialyzed in acidified deionized water for 3 days, then dialyzed in deionized water for another 0.5 day, and finally placed in a freeze dryer for freeze drying to obtain a yellow solid.

[0054] (3) 6 g of gelatin was added to 600 mL of deionized water at 80°C and stirred thoroughly. 10 g of NHS and 3 g of EDS powder were added to the above solution and stirred evenly, and the pH was adjusted to 5 with hydrochloric acid solution. Then 5 g of PBA powder was added and stirred in a water bath at 45°C for 48 h. The resulting solution was dialyzed in deionized water for 3 days and then freeze-dried.

[0055] (4) 2 g of PVA powder was added to 20 mL of deionized water solution and dissolved at 100 °C. 0.2 g of modified chitosan was added to the dissolved PVA solution and stirred for 2 h to obtain solution A. Then GPBA was prepared into a 12.5 wt% solution and 10 mg / mL of MXene@EGCG-Mg 40 μL was added to obtain solution B. Solutions A and B were mixed in a volume ratio of 1:1 and placed in a -80 °C refrigerator for 48 h, and thawed at room temperature to obtain a conductive hydrogel.

[0056] 2. Conductive hydrogel performance determination

[0057] (1) The electrochemical properties of the hydrogel patch were tested using the double-probe method using an electrochemical workstation (CHI660C). The hydrogel was sandwiched between two copper sheets for measurement. During the impedance measurement, the voltage was kept constant at 50 mV and the frequency range was 10 6 -10 -1 Hz.

[0058] (2) The antioxidant properties of the hydrogel components were tested using the DPPH free radical scavenging method. First, a DPPH solution was prepared and stored in a dark place. Then, the hydrogel was prepared into a 2.0 mg / mL solution. After the DPPH solution was mixed with 100 μL of the sample solution, it was placed in the dark for 30 to 120 minutes. Finally, the solution was scanned using an ELISA reader.

[0059] After 7 days of culture, PC12 cells were washed 3 times with PBS, fixed with 4% paraformaldehyde for 20 minutes, and permeabilized with 0.3% TritonX-100 for 5 minutes. After blocking with 1% BSA for 1 hour, cells were incubated with diluted primary antibody (Tuj1) at 4°C overnight, and then incubated with secondary antibody at room temperature for 1 hour. Cells were washed 3 times with PBS and stained with DAPI for 5 minutes. Finally, cells were examined with a laser scanning confocal microscope.

[0060] 3. Experimental results

[0061] Figure 6The results show that the conductivity of the hydrogel prepared by the present invention has an electrical conductivity that matches that of nerve cells, wherein the PCP group represents a hydrogel with a nanosheet concentration of 0 mg / mL, the PCPM1 group represents a hydrogel with a nanosheet concentration of 0.2 mg / mL, the PCPM2 group represents a hydrogel with a nanosheet concentration of 0.4 mg / mL, and the PCPM3 group represents a hydrogel with a nanosheet concentration of 0.6 mg / mL; the transmission electron micrograph of the prepared modified nanosheet solution is shown in Figure 1 A (200nm); conductive hydrogel gelation photos are shown in Figure 2 The free radical scavenging ability of the prepared hydrogel is shown in Figure 3 ; The immunofluorescence image of the prepared hydrogel promoting the proliferation and development of neural cells is shown in Figure 4 , relative fluorescence area Figure 5 .

[0062] In summary, the conductive hydrogel prepared by the present invention has high electrical conductivity and the ability to scavenge free radicals, can play an anti-inflammatory role, and can promote the proliferation of nerve cells and promote nerve repair.

[0063] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A method for preparing a conductive hydrogel, characterized in that: The following steps are involved: preparing a MXene nanosheet dispersion, and sequentially adding polyphenol and magnesium ions into the MXene nanosheet dispersion to obtain a modified nanosheet solution; The modified chitosan is mixed with polyvinyl alcohol to obtain solution A; The modified nanosheet solution is mixed with the gelatin modified with phenylboronic acid to obtain a solution B; The solution A and the solution B are mixed and reacted, then refrigerated at low temperature, and the conductive hydrogel is obtained after thawing.

2. The preparation method according to claim 1, characterized in that: The modified nanosheet solution is prepared, comprising the following steps: adding LiF to a hydrochloric acid solution, adding Ti3AlC2 and mixing; collecting the mixed precipitate, centrifuging and washing with deionized water until the pH value of the supernatant reaches 6; collecting the sediment obtained after centrifugation, ultrasonically dispersing under an Ar environment and centrifuging, collecting the solution, and obtaining a MXene nanosheet dispersion; dropping a gallic acid or tannic acid solution into the MXene nanosheet dispersion and mixing, then dropping a MgCl2·6H2O solution, mixing, centrifuging and washing, and obtaining the modified nanosheet solution.

3. The preparation method according to claim 1, characterized in that: The preparation method of the modified chitosan comprises the following steps: dissolving dihydrocaffeic acid and then adding it into a chitosan solution to obtain a mixed solution 1; dissolving 1-ethyl-(3-dimethylaminopropyl)carbodiimide and N-hydroxysulfosuccinimide in a mixed solution of ethanol and deionized water to obtain a mixed solution 2, adding the mixed solution 2 into the mixed solution 1, introducing Ar and reacting to obtain a product solution, first dialyzing it in acidified deionized water, then dialyzing it in deionized water, and finally freeze-drying it.

4. The preparation method according to claim 1, characterized in that: The preparation method of the solution A comprises: dissolving the polyvinyl alcohol powder, adding the modified chitosan into the dissolved polyvinyl alcohol solution, and mixing to obtain the solution A.

5. The preparation method according to claim 1, characterized in that: The preparation method of the solution B comprises: preparing a 12.5 wt % solution of phenylboronic acid-modified gelatin, and adding the modified nanosheets thereto to obtain the solution B.

6. The preparation method according to claim 1, characterized in that: The solution A and the solution B are mixed and reacted in a volume ratio of 1:

1.

7. The preparation method according to claim 1, characterized in that: The low temperature refrigeration is to place the mixture at -80°C for 12 to 48 hours.

8. The conductive hydrogel prepared by the preparation method according to any one of claims 1 to 7.

9. Use of the conductive hydrogel according to claim 8 in preparing a hydrogel having extracellular matrix-mimicking and anti-inflammatory effects.

10. Use of the conductive hydrogel according to claim 8 in preparing a hydrogel that promotes the proliferation and repair of nerve cells.

Citation Information

Patent Citations

  • MXene material reinforced conductive hydrogel

    CN111748107A

  • Preparation method and application of MXene-based autocatalytic conductive hydrogel dressing

    CN115068673A

  • MXene hydrogel used for sensing signal detection and having high mechanical strength and degradation recycling performance and preparation method thereof

    CN115873269A

  • Conductive hydrogel based on extracellular matrix, preparation method and application

    CN118221965A

  • Self-repairing conductive hydrogel based on modified MXene as well as preparation method and application of self-repairing conductive hydrogel

    CN118755148A

Cited By

  • Composite hydrogel based on extracellular matrix and MXene material as well as preparation method and application of composite hydrogel

    CN121490131A

  • Composite hydrogel based on extracellular matrix and mxene material, and preparation method therefor and use thereof

    WO2026162070A1